Análisis de los recursos naturales del sitio La Puntilla, para el desarrollo turístico local. - Blacio Gualpa, Silvana Cristina; Pillacela Caivinagua, Lorena Elizabeth (My University, 2021)
Natural resources promote the conservation of sustainable and sustainable tourism in the La Puntilla Community, which is made up of several tourist attractions that at the moment are not adequate to offer a type of tourism that benefits the community, this being essential for the empowerment of the entire collective. The main objective of this integrative project is to determine the tourist potential of the existing natural resources of the La Puntilla Site through the research instrument such as the interview directed towards the main local actors so that it is a development of receptive tourism, the same as generate inclusive participation between the community and the governance creating prosperous alliances that stipulate knowledge and skills aimed at strengthening capacities, also identifying the existence of the Island of the birds and the mangroves that are around the beach that have unique riches the which can intervene with different tourist activities. The method used is the descriptive and explanatory design because the qualities that attractiveness possesses are detailed, which manage to determine the actions to be carried out; With the qualitative approach, this category determines the techniques that lead to the achievement of the research, it is qualitative in that it is studied about tourism in natural areas, the information obtained was analyzed through the interaction that was obtained with the Tourism Analyst and Parish President for what it was considered that there are possibilities of generating tourism together with the support of other government entities. It was possible to identify that La Puntilla beach has several natural attractions that can be used to promote tourist activity, this being an ideal potential to generate environmental, economic, and social benefits that can obtain opportunities towards an improvement in the tourist plant, infrastructure and in addition to implementing programs, events, among others, so as to increase the influx of tourists, positioning the beach as one of the best in the cantón. For certain authorities, the main thing for there to be local development in any territory, a situational diagnosis must be made with a comprehensive development proposal that sustains tourism as the axis for the development of the strengthening of the local chain, which turns out to have verified information on the various situations that the community goes through, therefore, tourism planning is also required, which starts from the elaboration of projects, elaboration of a schedule with all the activities to be executed and the budget requirement by the public sector or the private sector, all the proposed actions achieve that the community work with a single purpose, for this reason it is recommended to maintain the training in different topics such as tourist guidance, multipurpose waiter and creative cuisine directed towards the community members who are an important part of the attraction because they know the information on existing species. As to flora and fauna, in this way the influence and motivation can be given to carry out tourism-oriented activities or, in turn, to be able to implement those activities in their productive environment.
Los recursos naturales fomentan la conservación del turismo sustentable y sostenible de la Comunidad La Puntilla que está integrado por varios atractivos turísticos que por el momento no se encuentran adecuados para ofertar una modalidad de turismo que beneficie a la comunidad, siendo esto esencial para el empoderamiento de todo el colectivo. El principal objetivo de este proyecto integrador es determinar la potencialidad turística de los recursos naturales existentes del Sitio La Puntilla mediante el instrumento de investigación como es la entrevista dirigida hacia los principales actores locales, de modo que sea un desarrollo del turismo receptivo, el mismo que genera una participación integradora entre la comunidad y la gobernanza creando alianzas prósperas que estipulen conocimientos y habilidades orientadas a fortalecer las capacidades, asimismo identificar la existencia de la Isla de las aves y del manglar que se encuentran alrededor de la playa que disponen de riquezas únicas las cuales pueden intervenir con diferentes actividades turísticas. El método utilizado es el diseño descriptivo y explicativo debido a que se detallan las cualidades que posee el atractivo los cuales logran determinar las acciones a realizar; con el enfoque cualitativo esta categoría determina las técnicas que encaminan en la consecución de la investigación, es cualitativo en cuanto se estudia acerca del turismo en áreas naturales, la información obtenida se analizó a través de la interacción que se obtuvo con la Analista de Turismo y Presidenta Parroquial por lo que se consideró que existen posibilidades de generar el turismo junto con el apoyo de otras entidades gubernamentales. Se logró identificar que la playa La Puntilla posee varios atractivos naturales que pueden ser aprovechados para fomentar la actividad turística siendo este un potencial idóneo para generar beneficios ambientales, económicos y sociales los mismos que pueden obtener oportunidades hacia un mejoramiento en la planta turística, infraestructura y además de implementar programas, eventos entre otros, de modo que incremente la afluencia de turistas posicionando a la playa como una de las mejores del cantón. Para ciertas autoridades lo primordial para que exista un desarrollo local en cualquier territorio se debe realizar un diagnóstico situacional con una propuesta íntegra de desarrollo que sostenga el turismo como eje para el desarrollo del fortalecimiento de la cadena local, el cual resulta tener información verificada de las diversas situaciones que atraviesa la comunidad, por ende, también se requiere la planificación turística que parte de la elaboración de proyectos, elaboración de un cronograma con todas las actividades a ejecutarse y el requerimiento de presupuesto por parte del sector público o del sector privado, todas las acciones planteadas logran que la comunidad trabaje con un solo propósito, por tal razón se recomienda mantener las capacitaciones en diferentes temáticas como pueden ser en guianza turística, mesero polivalente y cocina creativa dirigidas hacia los comuneros que son parte importante del atractivo debido que conocen la información de las especies existentes como flora y fauna, de esta manera puede darse la influencia y motivación a ejercer actividades orientadas al turismo o a su vez poder implementar esas actividades a su entorno productivo.
Keywords: RECURSOS NATURALES; FACTIBILIDAD